Pełnomocnik małoletniego pokrzywdzonego w postępowaniu karnym - postulaty de lege ferenda. - Flis-Świeczkowska, Marta Małgorzata (Studia Prawnoustrojowe, 2021)
The article is a kind of a response to the press conferences organised by the Ministry of Justice on the 21st February 2021 announcing, that Ministry of Justice had prepared complementary project of 21 changes in the legislation, make the law more child-friendly. The study contains numerous de lege ferenda demands concerning changes in the rules regulating the issue of representing a child in a criminal proceeding. The author proposes for example, simplification and harmonisation of issues of representation of minor victims, and thereby resignation from the participation of the guardian ad litem in the criminal proceeding, while introducing an instutution of mandatory attorney.